Low CTE, low puffing needle coke
Patent Information
- Application Number
- JP2021546589
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-09-17
- Filing Date
- 2020-09-02
- Publication Date
- 2025-03-12
- Estimated Expiration
- 2040-09-02
AI Technical Summary
【0018】 本発明によれば、水素供与性の小さいニードルコークス主原料油に水素供与性の大きい副原料油をコーキングし、得られた生コークスをか焼すること、また、細孔構造及び組織構造を制御して特定のコークス構造とすることで、低CTE、低パッフィングニードルコークスを安定して得ることができる。
Smart Images

Figure 0007644711000003 
Figure 0007644711000004 
Figure 0007644711000005
Abstract
Description
[Technical field]
[0001] The present invention relates to a low CTE, low puffing needle coke and an artificial graphite electrode for electric steelmaking. [Background technology]
[0002] Needle coke is generally produced from petroleum-based heavy oil or coal tar-based heavy oil as a raw material, and is used as an aggregate for artificial graphite electrodes for electric steelmaking. The graphite electrodes are produced by adjusting needle coke to a predetermined particle size, kneading it with binder pitch, extrusion molding, and then primary firing, impregnation, secondary firing, and graphitization.
[0003] Graphite electrodes are required to have a low coefficient of thermal expansion (CTE) in order to withstand harsh environments such as high-temperature atmospheres. A low CTE reduces electrode wear during electric steelmaking, which contributes to reducing the cost of electric steelmaking.
[0004] The graphitization process in the graphite electrode manufacturing process is a heat treatment at a high temperature of around 3000°C, and is generally done using an LWG furnace (a direct current furnace). When graphitizing in an LWG furnace, the temperature rise rate is fast, which causes gas to be generated from the graphite electrode material at a high rate, making it prone to an abnormal expansion phenomenon known as puffing. This puffing reduces the density of the electrode and can sometimes cause it to break. For this reason, methods of manufacturing needle coke to reduce puffing and puffing inhibitors to be added during electrode manufacturing have been investigated.
[0005] It is generally believed that the CTE is lower when the needle coke has a more uniform texture and more fine cracks. The hexagonal carbon network plane direction of the graphite structure, which is the crystalline structure that constitutes needle coke, has a smaller thermal expansion than the stacking direction, so it is believed that an electrode with a low CTE will have its plane direction aligned in the longitudinal direction of the electrode. It is also believed that the presence of fine cracks acts to mitigate thermal expansion, resulting in a low CTE. Puffing is generally believed to be caused by gas pressure resulting from the vaporization of compounds derived from nitrogen and sulfur in needle coke under high temperature conditions.
[0006] What is required for needle coke for artificial graphite electrodes is low CTE during electrode use and low puffing during electrode production. Conventional methods for producing low CTE, low puffing needle coke include the following technologies.
[0007] Patent Document 1 describes a method for reducing puffing by removing puffing-causing substances by hydrogenating a feed oil and removing nitrogen and sulfur from the feed oil, and for reducing CTE by exhibiting favorable carbonization behavior due to reduction in oxygen and sodium and reduction in viscosity at high temperatures due to an increase in naphthene rings. Patent Document 2 describes a co-carbonization method in which coal tar pitch from which quinoline insolubles have been removed is mixed with petroleum-based heavy oil adjusted to a specific property and coked to reduce puffing by diluting the nitrogen and sulfur components of puffing-causing substances, and a balance between carbonization rate and gas generation is obtained to generate an anisotropic structure showing a low CTE, thereby reducing CTE. Patent Document 3 describes a method for obtaining needle coke with low CTE and low puffing by mixing two or more types of feed oil to generate a good bulk mesophase and generate gas for crystal orientation during solidification. Patent Document 4 and Non-Patent Document 1 describe that calcination in two stages results in low CTE and low puffing due to the change in coke structure that occurs during calcination. Patent Document 5 describes that needle coke with low CTE and low puffing can be produced by increasing the number of micropores by re-calcining coke that has been calcined once in an oxidizing atmosphere. Patent Document 6 describes a method for producing needle coke with low CTE and low puffing by mixing coal tar heavy oil and petroleum heavy oil from which quinoline insolubles have been removed, coking the mixture, and further calcining the mixture in two stages.
[0008] As described above, it is known that low CTE, low puffing needle coke can be obtained by upgrading feedstock oil through hydrogenation, cocarbonization in which two or more types of feedstock oil are mixed and coked, two-stage calcination, recalcination in an oxidizing atmosphere, and combinations of these. Although it is not a method for reducing CTE or puffing, Patent Document 7 describes that adding a hydrogen donor solvent to low-temperature tar pitch and then heat-treating and thermally reforming it can be reformed to a quality suitable for use as a feedstock oil for needle coke. Non-Patent Document 2 proposes the Proton Donor Quality Index (PDQI) as an evaluation of hydrogen donor property, but this is an evaluation of a circulating solvent in a coal hydroliquefaction reaction, and there is no teaching that it is useful as an index for improving the quality of needle coke. [Prior art documents] [Patent documents]
[0009] Patent document 1: Japanese Patent Application Laid-open No. 149690 / 1983 Patent document 2: Japanese Patent Application Laid-Open No. 4-145193 Patent document 3: WO2009 / 1610 Patent document 4: Japanese Patent Application Laid-Open No. 52-29801 Patent Document 5: JP-A-61- 218686 Publication number Patent Document 6: Japanese Patent Application Laid-Open No. 5-163491 Patent document 7: WO2011 / 48920 [Non-patent literature]
[0010] [Non-Patent Document 1] Carbon Vol.19 No.5 pp.347-352 [Non-Patent Document 2] Fuel Association Journal, 65, 12, p.1012-1019, 1986 Summary of the Invention [Problem to be solved by the invention]
[0011] It is known that low CTE, low puffing needle coke can be obtained by using reformed feedstock oil, co-carbonization using two or more types of feedstock oil, and changing the calcination conditions. However, there is a demand for a more stable production of low CTE, low puffing needle coke while responding to changes in the properties of the feedstock oil. In artificial graphite electrodes, it is needle coke that exhibits low CTE and low puffing. By clarifying what needle coke structure contributes to low CTE and low puffing, it is believed that it will be possible to produce more stable low CTE and low puffing by combining the selection of feedstock oil, coking conditions, and calcination conditions. The present invention provides a needle coke with low CTE and low puffing properties by limiting the properties of the main feedstock oil and the auxiliary feedstock oil in a method for producing a low CTE, low puffing needle coke by mixing two or more types of feedstock oil and coking the mixture. In addition, the present invention provides a needle coke with low CTE and low puffing by controlling the needle coke structure obtained after coking and calcination to a specific structure. [Means for solving the problem]
[0012] The present inventors have conducted extensive research to solve the above-mentioned problems, and as a result have discovered that, in order to reduce CTE and puffing, a needle coke with low CTE and low puffing can be obtained by mixing a main needle coke feedstock oil with low hydrogen donating property with a secondary feedstock oil with high hydrogen donating property, and then coking and calcining the resulting mixed oil. They have also discovered that a needle coke with low CTE and low puffing can be obtained by controlling the needle coke to have a specific structure by selecting the raw materials, coking conditions, and calcination conditions, and thus completed the present invention.
[0013] That is, the present invention provides a low CTE, low puffing needle coke, which is characterized by mixing 100 parts by weight of a main needle coke feedstock oil, which is a coal tar heavy oil or a petroleum heavy oil having a low hydrogen donor property and a PDQI value of less than 5.0 as calculated by formula (1), with 10 to 80 parts by weight of a secondary feedstock oil having a high hydrogen donor property and a PDQI value of 5.0 or more as shown by formula (1), coking the mixture, and calcining the resulting raw coke. [Formula (1)] PDQI = H% × 10 × (HNβ / H) Here, H% is the amount of hydrogen (wt%) determined by elemental analysis, and HNβ / H is 1 This is the ratio of β-naphthenic hydrogen to total hydrogen measured by H-NMR.
[0014] The low CTE, low puffing needle coke of the present invention preferably has a needle coke structure index for CTE (NCSIC) shown in formula (2) of greater than 25.0 and a needle coke structure index for puffing (NCSIP) shown in formula (3) of greater than 5.0. [Formula (2)] NCSIC=((Lc / d002)+(open pore ratio)) / (σ(θ)) Here, Lc is the crystallite size, d002 is the interplanar spacing, and σ(θ) is the standard deviation of the average orientation angle. [Formula (3)] NCSIP=(open pore amount / closed pore amount)+(HIT / 1000) / EIT Here, HIT is the indentation hardness, and EIT is the indentation elastic modulus.
[0015] The low CTE, low puffing needle coke of the present invention is preferably made from a main feedstock oil that is a de-QI pitch with low hydrogen donating ability obtained by distilling and de-QIing coal tar. In particular, it is preferably made from a main feedstock oil that is a de-QI pitch with low hydrogen donating ability and a PDQI value of less than 2, calculated by the formula (1), obtained by distilling and de-QIing coal tar.
[0016] The low CTE, low puffing needle coke of the present invention preferably has a crystallite size Lc of 4.0 to 10.0 nm, a lattice spacing d002 of 0.340 to 0.350 nm, an open pore ratio of 0.15 to 0.40, and a standard deviation σ(θ) of the average orientation angle of 0.01 to 0.85. Open pore volume: 0.040~0.070cm 3 / g, and the closed pore volume is 0.001 to 0.015 cm 3 / g, the indentation hardness HIT is 800 to 1500 MPa, and the indentation elastic modulus EIT is 5.0 to 15.0 GPa.
[0017] In the present invention, the crystallite size Lc and interplanar spacing d002 in formula (2) are measured by XRD and obtained by analysis using the Gakushin method, the open pore ratio is calculated as the ratio of the volume of pores having a diameter of 1 to 10 μm to the volume of pores having a diameter of 120 μm or less measured by mercury porosimetry, and the standard deviation σ(θ) of the average orientation angle is calculated as the standard deviation that is an index of the variation in the orientation angle measured using a birefringence meter. Effect of the Invention
[0018] According to the present invention, a needle coke with a low CTE and low puffing can be stably produced by coking a needle coke main feedstock oil with a low hydrogen donating ability with a secondary feedstock oil with a high hydrogen donating ability, calcining the obtained raw coke, and controlling the pore structure and texture structure to give a specific coke structure. [Brief description of the drawings]
[0019] [Figure 1] 1 is a displacement-load curve in the measurement with a microhardness tester. [Diagram 2] 1 is a displacement-load curve of the needle coke of Example 1. [Diagram 3] 1 is a displacement-load curve of the needle coke of Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] The important factors of needle coke structure with respect to the CTE of needle coke are considered to be crystallinity, pore volume, texture orientation, etc. Most of these are formed during the coking process. In the process of heating the feedstock oil and coking it, organic molecules undergo repeated dehydrogenation polycondensation reactions, and in the process of lamination, mesophase spherulites with optical anisotropy are generated, which are known to have optical anisotropic textures through growth and coalescence. It is known that the viscosity of the system increases as the growth and coalescence of the mesophase progresses during the coking process, but if the balance between the increase in viscosity of the system and the growth and coalescence of the mesophase is lost and the viscosity increase occurs first, the mesophase cannot grow sufficiently, resulting in low crystallinity, and the crystallinity develops as the low viscosity region continues so that the growth and coalescence of the mesophase occurs sufficiently. In addition, just before the end of coking, the shear force from the generated gas and introduced gas orients the texture in one axis direction, improving the orientation of the optical anisotropic texture. Hydrogenated feedstock is an effective feedstock for these CTE-influencing factors. As a result of examining the difference between hydrogenated feedstock and non-hydrogenated feedstock, it was found that hydrogenated feedstock has a PDQI value of 0.01, which is expressed by the formula (1). Non-hydrogenated feedstock It was found that the CTE of the hydrogenated feedstock is larger than that of the hydrogenated feedstock, that is, the hydrogen donor is a characteristic of the hydrogenated feedstock. It was found that needle coke with a lower CTE can be produced by preparing a feedstock with a particularly large hydrogen donor among the hydrogenated feedstocks. The reason why needle coke with a lower CTE can be obtained by using a feedstock with a large hydrogen donor is not clear, but when a feedstock with a large hydrogen donor is used, naphthene hydrogen is transferred during coking, so the low viscosity region during coking continues, sufficient mesophase growth and coalescence progresses, and more gas is generated. The shearing of the gas just before the end of coking also improves the orientation of the optical anisotropic texture. However, if a feedstock oil with a high hydrogen donor is used alone as a feedstock oil, it is expected that the boiling point is lower than that of the main feedstock oil with a low hydrogen donor, and the amount of gas generated will be too large, so that raw coke cannot be obtained, or even if it is obtained, the yield will be low. On the other hand, by using a mixed feedstock oil in which a feedstock oil with a low hydrogen donor property, which is normally used, is used as the main feedstock oil and a feedstock oil with a high hydrogen donor property is used as the secondary feedstock oil, the naphthene hydrogen in the secondary feedstock oil is transferred to the aromatic rings of the main feedstock oil, and it becomes possible to continue the low viscosity region in which the main feedstock oil, which alone does not sufficiently grow and coalesce, can sufficiently develop, and it is thought that the orientation is also improved by the gas generated from the secondary feedstock oil with a high hydrogen donor property. In addition, the secondary feedstock oil with a high hydrogen donor property plays the role of a reaction adjuster, and by increasing or decreasing the amount, it is possible to adjust the improvement of characteristics. Therefore, it is preferable that the secondary feedstock oil with a high hydrogen donor property be mixed with 100 parts by weight of the main feedstock oil with a low hydrogen donor property in an amount of 10 parts by weight or more and 80 parts by weight or less. More preferably, it is from 20 parts by weight to 50 parts by weight, and further preferably, it is from 25 parts by weight to 45 parts by weight. By selecting the needle coke feedstock oil and at the same time adjusting the coking and calcination conditions appropriately to adjust the needle coke structure and make it suitable for low CTE and low puffing, further property improvements can be expected in addition to those achieved by the feedstock oil.
[0021] The structure of the needle coke obtained through raw material selection, coking, and calcination is considered to be most related to the CTE and puffing characteristics. The coke structure is evaluated by XRD to determine the degree of crystallinity development, birefringence to determine the orientation of the optically anisotropic structure, and mercury porosimetry to determine the amount of pores. It is considered possible to quantify the structure of the low CTE needle coke by using the needle coke structure index (Equation (2)) related to the CTE obtained from each evaluation result. When the crystallinity is developed, the crystallite size Lc is large and the interplanar spacing d002 is narrow, so that it can be considered that the crystallinity is developed when Lc / d002 is large. The crystallite size Lc is preferably 5.5 nm or more, more preferably 6.0 nm or more. The standard deviation σ(θ) of the average orientation angle θav measured from the birefringence is smaller when the orientation is high, indicating that the orientation is uniform, and therefore it is considered that the smaller σ(θ) is, the more uniform the orientation of the coke. The standard deviation σ(θ) is preferably less than 0.80, more preferably less than 0.70. It is considered that when the ratio of pores of 1 to 10 μm to pores of 120 μm or less is high, it acts as a relaxation site during expansion and contributes to a low CTE. The ratio of pores of 1 to 10 μm to pores of 120 μm or less is called the open pore ratio. The open pore ratio is preferably in the range of 0.15 to 0.40, more preferably 0.30 or more, and even more preferably 0.33 or more.
[0022] NCSIC is a numerical expression of the coke structure suitable for a low CTE, based on the coke structure's crystallinity, orientation, and pore volume. The higher this value is (more developed crystallinity, higher orientation, and more pore volume), the lower the CTE of the needle coke is considered to be.
[0023] Important factors in needle coke puffing are the causative substances, nitrogen and sulfur, in the needle coke. It is known that puffing can be reduced by reducing the gas causative substances, nitrogen and sulfur. However, what kind of needle coke structure is effective in reducing puffing? Although it is known that a large amount of pores is useful, other structures have not been clear. The present inventor has found that the amount of pores that serve as escape routes for the generated gas and the coke strength that can withstand gas pressure are important, and that the coke structure of a low puffing needle coke needs to be optimal in both the pore structure that allows the gas generated during puffing to escape and the organizational structure related to the strength that can withstand gas pressure.
[0024] Nitrogen and sulfur contents are derived from the feedstock oil, so low-nitrogen and low-sulfur feedstock oils are required, but in recent years, the nitrogen and sulfur contents in feedstock oils have increased, making it difficult to select feedstock oils. By adding secondary feedstock oils with high hydrogen donor properties, mild hydrodesulfurization and denitrogenation can be expected during coking, so the hydrogen donor properties of secondary feedstock oils are an important factor for selecting secondary feedstock oils.
[0025] The pore volume and strength can be appropriately changed depending on the coking or calcination conditions. Regarding the coke structure index suitable for low puffing (Equation (3)), it is considered that the coke structure suitable for puffing can be quantified by using two pore volumes, the open pore volume obtained from mercury porosimetry and the closed pore volume calculated from the true density and apparent density, the indentation hardness HIT calculated from the applied load and the indentation depth obtained from a microhardness tester, and the indentation elastic modulus EIT, which is the degree of recovery after unloading. In the present invention, the indentation hardness HIT is preferably 800 to 1500 MPa, more preferably 900 to 1400 MPa. The indentation elastic modulus EIT is preferably 5.0 to 15.0 GPa, more preferably 8.0 to 13.0 GPa.
[0026] A needle coke with low puffing can be obtained by optimizing the pore structure and the structural structure with respect to strength. The pore structure requires a large amount of open pores that are connected to the outside of the coke, and a small amount of closed pores that are not connected to the outside. The structural structure with respect to strength to withstand gas pressure requires a coke structure that is highly resistant to deformation due to external forces (hard structure) and flexible (low elastic modulus) that can easily recover after deformation due to external forces, specifically, a coke structure in which the orientation of the optical anisotropic structure is disordered at the micron size, but is aligned at the submicron to nano size. As for the pore structure, it is considered that puffing can be reduced by having a large amount of pores that serve as escape routes for gas when nitrogen and sulfur are vaporized as gas during graphitization. It is considered that a small amount of closed pores can reduce the amount of gas remaining in the coke and also reduce puffing. On the other hand, a coke structural structure with high strength is considered to be able to withstand the gas pressure during graphitization, or to easily recover even after deformation due to gas pressure, thereby reducing puffing. In coking, in order to develop optical anisotropy in the submicron to nano size range, in the early stage of coking, coking is performed at a low temperature or a hydrogenated raw material is used to develop a mesophase while maintaining a low viscosity state, and in the later stage of coking, in order to disrupt the orientation of the micron size optical anisotropic structure, the temperature, pressure, steam amount, or a combination of these are increased and the coking conditions are changed during the coking process to disrupt the system. By changing the coking conditions such as temperature, pressure, and steam amount during the process, the submicron to nano size optical anisotropy and the micron to millimeter size optical anisotropic structure can be changed, respectively, leading to an increase or decrease in the amount of closed pores in the coke obtained by the orientation of the structure structure. In calcination, methods such as calcination in two or more stages, high temperature calcination, and oxidative calcination can be used to increase the amount of open pores. In calcination in two or more stages, calcination is performed at a low temperature in the first stage, and after cooling, calcination is performed for the second or subsequent stages, which causes fine cracks to occur due to cooling and heating, thereby achieving an increase in open pores and a decrease in closed pores.In the case of high-temperature calcination, calcination at a higher temperature than usual causes greater shrinkage than in normal calcination, and cracks are generated due to stress, resulting in a larger amount of open pores. In the case of oxidation calcination, calcination with the introduction of an oxidizing gas oxidizes the surface of the needle coke, generating pores and increasing the amount of open pores. Open pore volume: 0.040~0.070cm 3 / g, preferably 0.050 to 0.065 cm 3 / g. The closed pore volume is 0.001 to 0.015 cm 3 / g, preferably 0.005 to 0.009 cm 3 / g range.
[0027] The needle coke of the present invention is obtained by coking a mixed feedstock oil, which is a mixture of a main feedstock oil with a low hydrogen donating ability and a secondary feedstock oil with a high hydrogen donating ability, and calcining the resulting green coke.
[0028] Examples of the main raw material oil for needle coke include coal tar heavy oil and petroleum heavy oil.
[0029] Examples of coal tar-based heavy oil include coal tar produced as a by-product during coke production, coal tar pitch obtained by distilling coal tar, and coal liquefied oil obtained by liquefying coal. It is preferable to use coal tar pitch from which quinoline insolubles have been removed, and which usually has a quinoline insoluble content of 0.1% or less. Coal tar pitch from which quinoline insolubles have been removed may be distilled and thermally modified to use as the raw oil. Examples of petroleum heavy oils include catalytic cracking oil, thermal cracking oil, atmospheric residual oil, vacuum residual oil, and ethylene bottom oil, with decant oil (FCC-DO), which is a heavy component of catalytic cracking oil, being particularly preferred. The feedstock oil may be a mixture of coal tar heavy oil and petroleum heavy oil, a mixture of by-product oils obtained in the coking process, or a thermally modified mixture of oils. These main feedstock oils have a PDQI value, which indicates hydrogen donating ability, of less than 5.0, preferably less than 1.0, and usually about 0.001, and thus have low hydrogen donating ability.
[0030] In the present invention, a secondary feedstock oil having a high hydrogen donating ability is used together with the main feedstock oil, and the main feedstock oil and the secondary feedstock oil are mixed together. As described above, the secondary feedstock oil used has a high PDQI value. The PDQI value is preferably 5.0 or more, more preferably 8.0 or more, and even more preferably 10.0 or more. The secondary feedstock oil can be a product obtained by hydrotreating coal tar heavy oil or petroleum heavy oil, which is the main feedstock oil. A preferred heavy oil is coal tar or a distillate thereof. More preferably, the heavy oil is a product obtained by partially hydrogenating a 300 to 600°C fraction obtained by distilling the main feedstock oil. In addition, even if the main feedstock oil of needle coke is not the starting feedstock oil, any oil adjusted to have a hydrogen donor value of 5 or more, preferably 10 or more, is suitable as a secondary feedstock oil. The hydrogenation conditions are preferably at 100°C or higher and lower than 300°C, with a hydrogen partial pressure of less than 5 MPa, and using a hydrogenation reactor using a hydrogenation catalyst; however, the present invention is not limited to this as long as the adjustment method satisfies the PDQI value.
[0031] The blending ratio of the main feedstock oil and the secondary feedstock oil is preferably 10 to 80 parts by weight of the secondary feedstock oil per 100 parts by weight of the main feedstock oil. More preferably, the secondary feedstock oil is 20 to 50 parts by weight, more preferably, 25 to 45 parts by weight. If the amount of the secondary feedstock oil is small, the hydrogen donor ability is low, and the desired needle coke with low CTE and low puffing cannot be obtained. On the other hand, if the amount of the secondary feedstock oil is too large, the cracking reaction of the secondary feedstock oil becomes dominant over the reaction between the main feedstock oil and the secondary feedstock oil, and the hydrogen of the secondary feedstock oil cannot be used to promote the growth and coalescence of the mesophase of the main feedstock oil, so that the desired needle coke with low CTE and low puffing cannot be obtained.
[0032] The coking of the mixed raw material oil can be performed by a known delayed coking method. For example, raw coke is obtained by coking at 450 to 550°C and a pressure of 0.2 to 0.8 MPa for 18 to 48 hours. The coking method can be a method in which the charging temperature is gradually changed during coking, the coking pressure is gradually changed, the amount of steam charged during coking is gradually changed, the raw material oil is divided into two, one raw material oil is fed into the coker at a low temperature from the bottom of the coker and the other raw material oil is fed into the coker at a high temperature from the side of the coker, the pressure during coking is increased and the amount of steam is increased more than usual, or a combination of these methods can be used.
[0033] A known method can be used to calcinate the raw coke. For example, a method of calcining at 800 to 1600°C using a rotary kiln, shaft furnace, or siliconite furnace can be used. Calcination may be performed in one stage or in two or more stages. Calcination may be performed at a high temperature or by blowing in an oxidizing gas.
[0034] The method for producing an artificial graphite electrode for electric steelmaking from the above-mentioned low CTE, low puffing needle coke may be a known method, and the electrode can be obtained through steps such as kneading with binder pitch, molding, primary firing, impregnation, secondary firing, and graphitization.
[0035] Next, the measurement conditions will be described. The feedstock oil for needle coke contains condensed polycyclic aromatic hydrocarbons with naphthenic ring structures, and the hydrogen in the naphthenic ring includes hydrogen (HNα) that is bonded to the carbon at the α position relative to the carbon in the aromatic ring, and hydrogen (HNβ) that is bonded to the carbon at the β position or higher. There are also hydrogens derived from alkyl groups that are bonded to the condensed polycyclic aromatics as substituents, and these also include hydrogen (Hα) that is bonded to the carbon at the α position and hydrogen (Hβ, etc.) that is bonded to the carbon at the β position or higher. There is also hydrogen (Ha) that is bonded to the carbon in the aromatic ring.
[0036] The identification of these hydrogens etc. 1 This is done by H-NMR measurement. 1 The H-NMR measurements were performed using chloroform as a solvent and TMS (tetramethylsilane) as a standard substance using a JNM-LA400 manufactured by JEOL Ltd., and the hydrogen fraction was calculated from the integral value of the obtained 1H-NMR spectrum. Hα, HNα, and HNβ were obtained 1 The chemical shifts were calculated by integrating the H-NMR spectrum at chemical shifts of 2.0 to 4.2, 3.0 to 4.2, and 1.5 to 2.0, respectively.
[0037] Carbon and hydrogen analyses (elemental analysis) of the main feedstock oils and the secondary feedstock oils were calculated in accordance with JIS M 8819, nitrogen in accordance with JIS K 2609, oxygen in accordance with JIS M 8813, and sulfur in accordance with JIS K 2541.
[0038] PDQI is calculated by the formula (1). H% is the amount of hydrogen (weight%) determined by elemental analysis, and HNβ / H is 1 This is the ratio of β-naphthenic hydrogen to total hydrogen measured by H-NMR. PDQI represents the maximum amount of donatable hydrogen (mg) of naphthene rings contained in 1g of solvent, and is expressed in mg / g.
[0039] The crystallite size Lc and interplanar spacing d002 obtained from XRD were calculated by measuring angles of 20 to 30° using an XRD device manufactured by Rigaku Corporation and performing crystallite size analysis using the Gakushin method.
[0040] The standard deviation σ(θ) of the orientation angle obtained from the measurement using a birefringence meter was measured by embedding needle coke particles of 1 to 2 cm in resin, polishing them with a polishing machine, and making them 8 mm thick with the needle coke exposed on the surface as a test piece. The exposed needle coke surface was measured using a Photonic Lattice birefringence meter PI-micro, with a resolution of 0.9 μm or 2.7 μm per pixel, and the retardation Re, average orientation angle θav, and standard deviation σ(θ) of the average orientation angle for one field of view were calculated from the retardation Re and orientation angle θ values for each pixel, and multiple fields of view were measured. The average value for the entire measured field of view was used as the evaluation value.
[0041] The mercury porosimetry of the needle coke was measured by dividing the needle coke into 2-5 mm pieces and measuring the pressure from 1.9 to 14400 psi (pore diameter equivalent: 0.017 to 120 μm) using an Autopore IV manufactured by Micromeritics. The pore volume relative to the pore diameter was calculated from the obtained pressure and mercury amount, and the pore volume of 1 to 10 μm was calculated and used as the open pore volume of the needle coke. The open pore ratio was calculated by dividing the pore volume of 1 to 10 μm by the pore volume of 120 μm or less. In Tables 1 and 2, the pore volume value means the total pore volume, and is the pore volume of 120 μm or less for calculating the open pore ratio.
[0042] The true density of the needle coke was measured in accordance with JIS K 2151. The apparent density was measured by crushing the needle coke with a jaw crusher, sieving it through an 8-16 mesh screen, and then measuring it in the same manner as for the true density. The closed pore volume was calculated using the following formula (4). [Formula (4)] Closed pore volume (cm 3 / g)= (1 / apparent density (g / cm 3 )―(1 / true density(g / cm 3 ))
[0043] The microhardness tester was used to measure the exposed surface of needle coke. A test piece was made by embedding needle coke particles measuring 1 to 2 cm in resin, polishing them with a polishing machine, and reducing the thickness to 8 mm with the needle coke exposed on the surface. The specific test conditions were as follows: using a Fisher Instruments FISHERSCOPE, HM2000, a Vickers indenter as the measuring probe, a maximum load of 2000mN, a loading speed of 300mN / s, a creep time of 2 seconds, and unloading at the same speed as the loading. Ten points were measured for each test piece, and the average value was used as the value for that test piece. Figure 1 shows a typical displacement-load curve. In order to measure the microstructural structure of needle coke, it is necessary to measure it in the region where the needle coke does not undergo plastic deformation (fracture) (elastic deformation region). In the displacement-load curve obtained in the test, the displacement must return to the origin after unloading, as shown in Figure 1. The indentation depth is the amount of displacement at the maximum load in the indentation test and varies depending on the test conditions and the measured substance. A depth just before the needle coke is destroyed is preferable. When measuring the needle coke of the present invention under the test conditions used here, a depth of 8 to 15 μm is preferable.
[0044] The indentation hardness HIT is calculated by the analysis software attached to the device using the following formula (5) from the maximum load and indentation depth of the indentation test in accordance with ISO 14577. If the coke is hard, it cannot be indented during the test, so HIT is considered to indicate a coke structure that has high resistance to the indenter, and an example of a hard coke structure is thought to be caused by a disorder in the orientation of the optical anisotropic structure of the coke structure. [Formula (5)] Indentation hardness HIT(MPa)=Fmax / Ap Here, Fmax is the maximum load, and Ap is the projected area where the indenter is in contact with the test piece.
[0045] The indentation elastic modulus EIT is calculated by the analysis software attached to the apparatus based on the slope of the initial unloading period from the maximum load of the indentation test using the following formula (6) in accordance with ISO 14577. This EIT is thought to be due to the fact that coke with a low elastic modulus is easily restored after unloading, and that the optical anisotropic texture of the coke structure, which is an example of a coke structure with a low elastic modulus, is well developed. [Formula (6)] Indentation elastic modulus EIT(GPa)= (1-(Vs) 2 ) / (1 / Er-1-(Vi) 2 / (Ei) Here, Vs is the Poisson's ratio of the sample, Vi is the Poisson's ratio of the indenter, Er is the reduced elastic modulus of the indentation contact, and Ei is the elastic modulus of the indenter.
[0046] The structural index NCSIC related to the CTE increases as the graphite crystallinity of the needle coke increases, the proportion of open pores increases, and the orientation of the pores increases. This index indicates that the needle coke is more suitable for achieving a low CTE. As described above, the NCSIC is preferably greater than 25.0, more preferably 27.0 or greater, and even more preferably 29.0 or greater.
[0047] The structural index NCSIP for puffing is larger the more open pores, the fewer closed pores, the harder the structure, and the lower the elastic modulus of the needle coke, and is an index indicating that the needle coke is more suitable for low puffing. As described above, the NCSIP is preferably greater than 5.0, more preferably 6.0 or greater, and even more preferably 7.0 or greater.
[0048] The nitrogen content in the raw coke and needle coke was measured in accordance with JIS M 8819. The sulfur content in the raw coke and needle coke was measured in accordance with JIS M 8813.
[0049] The CTE and puffing test pieces were prepared by crushing needle coke with a jaw crusher, sieving off 8-16 mesh, mixing the over-sieve and under-sieve, crushing it with a hammer crusher, and sieving it into 48-200 mesh and 200 mesh or less. Each was mixed at 40wt%, 35wt%, and 25wt%, and then kneaded with binder pitch (BP97, manufactured by C-Chem Co., Ltd.). The kneading was carried out using a kneader, mixing 30wt% of binder pitch with 100wt% of needle coke, and kneading for 20 minutes at 160℃ to obtain a kneaded product.
[0050] For puffing, the kneaded material was molded to obtain a molded body with a diameter of 20 mm and a length of 100 mm. This molded body was then fired at 900°C, impregnated with impregnating pitch (IP78, manufactured by C-Chem Co., Ltd.), and fired again at 900°C to prepare a test piece for puffing measurement. The puffing was measured by heating the test piece in an argon atmosphere in a Tammann furnace from room temperature to 2550°C at a heating rate of 10°C / min, measuring the elongation of the test piece in the longitudinal direction at 1500°C and 2500°C, and calculating the puffing from the following formula (7). [Formula (7)] Puffing (%) = (L2500-L1500) / L x 100 Here, L is the initial length of the test piece, L1500 is the length at a temperature of 1500°C, and L2500 is the length at a temperature of 2500°C.
[0051] For CTE, the kneaded material was extruded and molded into a molded body adjusted to a diameter of 20 mm and a length of 100 mm. The molded body was then fired at 900°C and graphitized in an argon atmosphere at 2550°C in a Tammann furnace to prepare a test piece. The CTE was measured by measuring the average thermal expansion coefficient of the prepared test piece from room temperature to 500°C. EXAMPLES
[0052] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to these examples.
[0053] Example 1 Coal tar was distilled, and the heavy component coal tar pitch obtained was subjected to solvent separation to remove quinoline insolubles, which was used as the main feedstock oil. The 300-600 ° C fraction obtained by distilling coal tar pitch from which quinoline insolubles had been removed, prepared in the same manner, was subjected to atmospheric distillation to obtain a secondary feedstock oil, which was then batch-hydrogenated at 200 ° C and 4.5 MPa in the presence of a hydrogenation catalyst (stabilized Ni). 35 parts by weight of secondary feedstock oil was mixed with 100 parts by weight of the main feedstock oil, and the mixed feedstock oil was coked at 0.6 MPa, with the coking charge temperature increased stepwise from 470 ° C to 530 ° C, and the steam ratio (amount of steam (g) / amount of feedstock oil (g)) increased stepwise from 0.15 to 0.30, to obtain green coke. The obtained green coke was calcined at 700 ° C in a nitrogen atmosphere, cooled once, and then calcined again at 1400 ° C to obtain needle coke. Test pieces for CTE and puffing were prepared from this needle coke. The property values of the obtained needle coke and test pieces are shown in Table 1.
[0054] Example 2 The same coal tar pitch as in Example 1 was used as the main feedstock oil, and the 300-600°C fraction obtained by distilling the coal tar at atmospheric pressure was batch-hydrogenated in the presence of a hydrogenation catalyst (stabilized Ni) at 200°C and 4.5MPa to obtain the secondary feedstock oil. 43 parts by weight of the secondary feedstock oil was mixed with 100 parts by weight of the main feedstock oil, and the mixed feedstock oil was coked at a coking charge temperature of 460°C in stages to 550°C, a pressure of 0.5MPa in stages to 0.65MPa, and a steam ratio of 0.10 in stages to 0.35, to obtain raw coke. After that, the same operation as in Example 1 was performed.
[0055] Example 3 The same coal tar pitch as in Example 1 was used as the main feedstock oil, and the fraction with a boiling point of 300 to 600 ° C. obtained by distilling the fluid catalytic cracking oil at atmospheric pressure was batch-hydrogenated in the presence of a hydrogenation catalyst (stabilized Ni) at a temperature of 250 ° C. and a pressure of 4.5 MPa to obtain a secondary feedstock oil. 100 parts by weight of the main feedstock oil and 45 parts by weight of the secondary feedstock oil were mixed, and the pressure was 0.5 MPa. The coking charge temperature was gradually increased from 470 ° C. to 500 ° C., while the steam ratio was gradually increased from 0.15 to 0.35, and coking was performed to obtain raw coke. After that, the same operation as in Example 1 was performed.
[0056] Comparative Example 1 The coal tar pitch of Example 1 was used as the main feedstock oil, and the 300-600°C fraction obtained by distilling the coal tar at atmospheric pressure was used as the secondary feedstock oil. 100 parts by weight of the main feedstock oil and 45 parts by weight of the secondary feedstock oil were mixed and coked under constant conditions of 500°C, 0.4 MPa, and a steam ratio of 0.12 to obtain raw coke. Thereafter, the same operation as in Example 1 was performed.
[0057] Comparative Example 2 The same main feedstock oil as in Example 1 was used, and the secondary feedstock oil was a 300-600°C fraction obtained by atmospheric distillation of a mixture of 70% by weight of the coal tar pitch used as the main feedstock oil in Example 1 and 30% by weight of fluid catalytic cracking oil. 100 parts by weight of the main feedstock oil and 45 parts by weight of the secondary feedstock oil were mixed and coked under constant conditions of 490°C, 0.4 MPa, and a steam ratio of 0.12 to obtain raw coke. Thereafter, the same operations as in Example 1 were performed.
[0058] Comparative Example 3 100 parts by weight of the main feedstock oil used in Example 1 was mixed with 100 parts by weight of the secondary feedstock oil used in Example 1, and the mixed feedstock oil was coked under constant conditions of 530°C, 0.5 MPa, and a steam ratio of 0.10 to obtain raw coke. Thereafter, the same operations as in Example 1 were carried out.
[0059] Tables 1 and 2 show the type and properties of the feedstock oil, and the characteristics of the raw coke and needle coke.
[0060] [Table 1]
[0061] [Table 2]
Claims
1. A method for producing needle coke using coal tar heavy oil or petroleum heavy oil as the main feedstock oil and a hydrotreated coal tar heavy oil or petroleum heavy oil as the secondary feedstock oil, comprising mixing 100 parts by weight of a needle coke main feedstock oil, which is coal tar heavy oil or petroleum heavy oil and has a low hydrogen donating property and a PDQI value of less than 1.0 as represented by formula (1), with 10 to 80 parts by weight of a secondary feedstock oil and has a high hydrogen donating property and a PDQI value of 5.0 or more as represented by formula (1), to produce coke, and calcining the obtained raw coke. [Formula (1)] PDQI=H%×10×(HNβ / H) Here, H% is the amount of hydrogen (wt%) determined by elemental analysis, and HNβ / H is 1 It is the ratio of β naphthenic hydrogen to total hydrogen measured by H-NMR.
2. 2. The method for producing a low CTE, low puffing needle coke according to claim 1, wherein the main feedstock oil is a de-QI pitch having a low hydrogen donating property obtained by distilling and de-QIing coal tar.
Citation Information
Patent Citations
Production of needle coke
JP1993001288A
Preparation of needle coke
JP1993239466A
Modified tar and method for producing modified tar, method for producing raw coke, and method for producing needle coke
JP2011089024A
Manufacturing method of hydrogenated coal tar pitch
JP2015193805A
Petroleum needle coke for graphite electrode and method for producing the same
JP2017019915A